SOCIAL ISOLATION DURING THE COVID-19 PANDEMIC AND ITS CONSEQUENCES ON MENTAL HEALTH - Hansmann Medeiros, Rogério (Health and Society, 2023)
OBJECTIVE: This article aims to identify the mental impacts caused by social isolation caused by the covid-19 pandemic. For greater understanding, it seeks to broadly conceptualize mental health, identify the impacts on people’s social life caused by social isolation and map the age range of people who have suffered the greatest impact. It aims to provide mental health professionals with an overview of the consequences of isolation on human behavior, so that in this way these professionals working in the public network can take advantage of the scientific conclusions obtained with this review. METHODOLOGY: This article is described on a bibliographical review carried out on the scientific findings published so far, facing certain difficulty due to the little scientific content published up to the moment we started this monograph. RESULTS AND COCLUSIONS: Mental health was duly conceptualized, and it should be noted that the World Health Organization maintains an outdated concept, due to the simple fact of dividing the physical, mental and social fields, differently from the current understanding of mental health, absence of diseases, involving the physical, mental and social fields, where the German school of psychology Gestalt, describes very well, informing that the set of the whole is greater than the sum of the individuals. Clearly, impacts on mental health were identified, pointing out that the more inhabitants in a household, the lower the anxiety stress index, mapping the age group of young people as the most susceptible to social isolation.